PENGARUH PERSEPSI REMAJA TENTANG KONFLIK ANTAR ORANG TUA DAN RESILIENSI TERHADAP DEPRESI DAN KECEMASAN - Sholichah, Mutingatu (Universitas Ahmad Dahlan, 2016)
AbstrackThe family plays a very important role in the development of children and adolescents, but not all families can provide an enabling environment for children to grow and develop optimally, such as family tinged conflicts between parents. This study was intended to findout the effects of adolescents perception about interparental conflict on anxiety and depression and the role of resilience to mediate those effects. Participants were 102 junior and senior highs school students aged 12-17 years old, who completed four scales used asinstruments in the study: T-Mas anxiety scale from Taylor, Kurcher Adolescent Depression Scale (KADS ) 11 items version, The Resilience Scale developed by Wagnild & Young, and The Children’s Perception of Interparental Conflict Scale (The CPIC) from Grych dan Finchman. Data obtained from 4 scales were analyzed with Path analysis. The findings indicated all hypotheses were accepted, that The Children’s Perception on Interparental Conflict shows a direct significant effect on anxiety as well as depression but the effect was not significant when mediated by resilience. Resilience plays an important role toprotect adolescence from adversity resulted from interparental conflict.Key words: anxiety, depression, internalizing problem,resilience